2021
DOI: 10.29303/jppipa.v7i2.654
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Blended Learning with A STEM Approach to Improve Student Scientific Literacy Skills During The Covid-19 Pandemic

Abstract: The Covid-19 pandemic has a positive impact on the blended learning system, especially the synchronous and asynchronous aspects of online learning. This study aims to obtain information about how to apply the blended learning model with the STEM approach to students' scientific literacy skills during the COVID pandemic. The research method used was pre-experiment with one group pretest-posttest design. This research was conducted at SMAN 1 Bojong Gede, Bogor Regency in the academic year 2020/2021. The research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
14
0
4
Order By: Relevance
“…While asynchronous learning refers to learning with communication outside of real-time, so it usually uses text, video, or audio chat. Text and digital tools that encourage asynchronous learning include videos, bulletin boards, reading, and writing or blogging activities (Lestari et al, 2021).…”
Section: Learningmentioning
confidence: 99%
“…While asynchronous learning refers to learning with communication outside of real-time, so it usually uses text, video, or audio chat. Text and digital tools that encourage asynchronous learning include videos, bulletin boards, reading, and writing or blogging activities (Lestari et al, 2021).…”
Section: Learningmentioning
confidence: 99%
“…Blended learning has been combined with various media, such as android (Mahendri et al, 2022) Google Classroom (Talibo et al, 2022), Edmodo (Sefriani et al, 2021, E-Learning, Video, and Podcast (Lestari et al, 2021). It was found that blended learning could effectively improve learning outcome (Sidabalok & Sinaga, 2021 ;Khairal Abd et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The BLM is a learning model that combines a faceto-face learning system with modern learning to improve students' learning abilities (Garner & Oke, 2015;Elvianasti et al, 2022;Lestari et al, 2021). The BLM reduces the estimation of conventional learning time in the classroom to increase students' active and autonomous learning abilities by combining the best features of face-to-face learning with online learning (Husamah, 2014).…”
Section: Introductionmentioning
confidence: 99%